A short course in foundation engineering - Simons, N. E. (Thomas Telford, 2000)
Although there are now a large number of computer programmes for solving all sorts of foundation design problems, the need to check these outputs by 'hand-calculation' has become vitally important. This book concentrates on getting the fundamentals right and then using them in practical applications.